The Influence of Personal Characteristics and Organizational Politics on Career Success of School Principals in Malaysia - Shahibudin, Ishak (2011)
Many factors have been identified as predictors of career success, but there is inconclusive evidence in relation of organizational politics to these factors. The primary purpose of this research is to examine the influence of personal characteristics and organizational politics on school principal’s intrinsic career success (career and life satisfaction) and extrinsic career success (salary attainment and number of promotion) in the context of public secondary school organizations. Specifically, this research investigated the degree to which four sets of predictor’s variables: human capital, political personality traits, political skill, political behavior, perception of politics influence career success of school principals. In addition, the study also examined the moderating influence of organizational politics perception on the relationship between individual attributes and career success. This study involves a quantitative analysis of school principals' self perception of their human capital, political personality traits, political skill, political behavior, perception of politics and career success. The data was obtained through mail survey method from 600 school principals. The response rate for the sample was 53 percent, resulting in a usable sample size of 312 participants. The data were analyzed by using descriptive statistics analysis, normality test, exploratory factor analyses, correlation analyses and regression analyses. Results of the study showed that school principals perceived the level of organizational politics in public secondary school in Malaysia is moderate. Five major findings of this study are as follows: (1) Human capital factors were positively and significantly influence extrinsic career success. (2) Political Personality traits were positively and significantly influence intrinsic career success factor. (3) Political skills were positively and significantly influence intrinsic career success. (4) Organizational politics behaviors were not significantly influence intrinsic and extrinsic career success. (5) The perception of organizational politics had a moderating influence on the relationship between networking political skill and salary attainment. Overall, the findings were not strong evidence to support that organizational politics has a strong influence on the career success of school principals. After all, extrinsic career success of a school principal was not influenced by organizational politics, but intrinsic career success was influenced by organizational politics. This study also confirms that there are difference profiles of variables related to extrinsic and intrinsic career success. Therefore, this study found little evidence for organization politics perceptions as moderator the personal characteristics and career success relationship. This study finding has viii contributed to current knowledge and understanding of career success from political perspective. The results thus serve to improve organizational career planning management and can help individuals to manage their career. Finally, the thesis discusses the implications of the study to theory and practice, limitations, and recommendations for future research.